Deficiency of Fhl2 leads to delayed neuronal cell migration and premature astrocyte differentiation - Kim, Soung Yung; Ludwig, Stephan; Schneider, Holm; Wixler, Viktor; Park, Jung; Völkl, Simon (Journal of Cell Science, 2019)
The four and a half LIM domains protein 2 (Fhl2) is an adaptor protein capable of mediating protein-protein interactions. Here, we report for the first time phenotypic changes in the brain of Fhl2-deficient mice. We showed that Fhl2 is expressed in neural stem cells, precursors and mature cells of neuronal lineage. Moreover, Fhl2 deficiency leads to delayed neuroblast migration in vivo, premature astroglial differentiation of neural stem cells (NSCs) in vitro, and a gliosis-like accumulation of glial fibrillary acidic protein (GFAP)-positive astrocytes in vivo that substantially increases with age. Collectively, Fhl2-deficiency in the brain interrupts the maintenance and the balanced differentiation of adult NSCs, resulting in preferentially glial differentiation and early exhaustion of the NSC pool required for adult neurogenesis.
CRIS-Team WoS Importer:2019-04-12